Small Area Estimates of Subjective Wellbeing: Spatial Microsimulation on the Australian Unity Wellbeing Index Survey - Cummins, Robert; Mohanty, Itismita; Tanton, Robert; Keegan, M; Keegan, Marcia (My University, 2013)
Subjective wellbeing is an indicator of how satisfied a person is with their life. It is becoming accepted as an indicator of happiness and overall wellbeing. This paper uses spatial microsimulation methods to estimate small area subjective wellbeing (SWB) in Australia. The procedure uses the Australian Unity Wellbeing Index survey and the 2011 Census data to derive small area estimates of SWB. Validation of the results shows that high and normal levels of SWB compare well to another source of SWB for small areas in the Murray Darling Basin, but levels of low SWB are not predicted as well, possibly due to the effect of local factors not available for the modelling on reducing SWB. Aggregate estimates compare well to HILDA estimates of SWB at a State level. These estimates are now available from the Australian Urban Research Infrastructure Network (AURIN) at the University of Melbourne.
NATSEM Working Paper 13/23
NATSEM Working Paper Series
Keywords: Satisfaction -- Life; Lifestyle; Satisfaction; Life; Lifestyle